coupled reservoir geomechanical simulation of co2 injection and ground deformation CMG - Amina, Hamini; Mohamed Riad Youcefi (Université Amar Telidji- Laghouat FACULTE : TECHNOLOGIE DEPARTEMENT : GÉNIE DES PROCÉDÉS, 2024)
In an attempt to prevent the release of large amounts of CO2 into the atmosphere resulting from the use of fossil fuels in power generation and other industries Carbon capture and sequestration (CCS) was introduced as a method to safe storage away from the atmosphere.This study seeks to implement a coupled reservoir-geomechanical modeling approach using CMG software to assess the geomechanical risks. A vertical injector well is used for CO₂ injection . from January 1, 2000, to January 1, 2010, including a 5-year shut-in period , to assess long-term reservoir response ,the results obtained are, increased pore pressure reduced effective normal stress, causing fractures and gas leakage into overburden layers by February 2002, with further saturation observed in top layers by December 2004 and January 2010 .
Gas engineering